2001
DOI: 10.1021/tx0101189
|View full text |Cite
|
Sign up to set email alerts
|

P450-Mediated Metabolism of 1-[3-(Aminomethyl)phenyl]-N-[3-fluoro-2‘-(methylsulfonyl)- [1,1‘-biphenyl]-4-yl]-3-(trifluoromethyl)-1H-pyrazole- 5-carboxamide (DPC 423) and Its Analogues to Aldoximes. Characterization of Glutathione Conjugates of Postulated Intermediates Derived from Aldoximes

Abstract: The in vivo and in vitro disposition of DPC 423, a highly potent, selective, and orally bioavailable inhibitor of blood coagulation factor Xa, has recently been described. Several metabolites, some of which were considered potentially reactive, were identified in rats. A novel GSH adduct, the structure of which was not determined conclusively, was isolated from bile of rats dosed with DPC 423. Herein, we describe the complete structural elucidation of this unique GSH conjugate employing LC/MS and high-field NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
2
36
2
Order By: Relevance
“…Additionally, several reports have appeared in the literature describing the metabolism of benzylamines and structural analogues and results have revealed that the benzylamine moiety was a metabolic soft spot. Oxidative deamination yielding the aldehyde was demonstrated to be a precursor of the corresponding acid metabolite, and the formation of the aldehyde intermediate and/or metabolite has been attributed to mitochondrial monoamine oxidase (MAO)-B. Acyl glucuronides, a carbamyl glucuronide, oxime, a glutathione adduct and N-acetylation were also reported (Timperio et al 2003;Mutlib et al 2001Mutlib et al , 2002aMutlib et al , 2002bMutlib et al , 2002cShaffer et al 2008). …”
Section: Discussionmentioning
confidence: 97%
“…Additionally, several reports have appeared in the literature describing the metabolism of benzylamines and structural analogues and results have revealed that the benzylamine moiety was a metabolic soft spot. Oxidative deamination yielding the aldehyde was demonstrated to be a precursor of the corresponding acid metabolite, and the formation of the aldehyde intermediate and/or metabolite has been attributed to mitochondrial monoamine oxidase (MAO)-B. Acyl glucuronides, a carbamyl glucuronide, oxime, a glutathione adduct and N-acetylation were also reported (Timperio et al 2003;Mutlib et al 2001Mutlib et al , 2002aMutlib et al , 2002bMutlib et al , 2002cShaffer et al 2008). …”
Section: Discussionmentioning
confidence: 97%
“…The discovery that nitrile oxide electrophiles can engage in such highly selective cellular interactions is unexpected given that nitrile oxides are regarded as one of the most reactive organic functional groups 41 . Indeed, the reactivity of nitrile oxides has previously precluded their isolation and investigation as protein-reactive electrophiles 42,43 . The biological utility of nitrile oxide electrophiles that we have now uncovered is predicated on the unique electrophile-masking elements present in the ML210 nitroisoxazole chemical pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of DPC423 was investigated extensively by Mutlib et al (10)(11)(12) in various species. In general, a number of metabolites were detected in samples of rat bile, urine, plasma, and microsomes.…”
Section: Drug Metabolism and Pharmacokineticsmentioning
confidence: 99%